Invisibilité des risques sanitaires et ambivalences des héritages industriels en Seine-Saint-Denis - Axelle Croisé; Alexis Sierra; Benjamin Lysaniuk (EchoGéo)
The significant industrialization of Seine-Saint-Denis has left a strong mark on its territory. However, its tangible and intangible marks are threatened. The urban, economic, social and political transformations have progressively affected the industrial history and the memory of sanitary work conditions. This paper is aimed at analysing the visibility of industry’s health impacts on workers and residents compared to the recognition of industrial heritage. In a context where the Seine-Saint-Denis region is already associated with many negative perceptions, we will focus on the "urban recycling" of these sites which contributes to render invisible the health consequences of industrial activities.